Ethnobotanical Research on Plants Utilized in Traditional Medicine for Treating Diabetes in the Gondwana Region of the Vindhyan Area in Madhya Pradesh, India - Mohammad Salim; Prabha Prajapati; I. P. Prajapati (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
This chapter focuses on the investigation of medicinal plants utilized for treating diabetes in the Gondwana region of the Vindhyan area in Madhya Pradesh, India. The study concentrates on districts like Sidhi, Shahdol, Umaria, and Anuppur. The paper provides descriptions of various plants, including their botanical and common names, family, growth habits, habitats, and the specific plant parts employed for managing sugar levels in humans.